(untitled) - Swonk, Diane (Hoboken, N.J., 2003)
The Passionate Economist: Finding the Power and Humanity Behind the Numbers, Swonk skillfully reveals how economics is not a hard science, but a behavioral science built on the foundation of human activity. A Washington insider, she presents her extremely knowledgeable perspective on the Federal Reserve and the power of money, and offers practical advice that will help you make wiser decisions on where to put your money.
Keywords: Economists,Nhà kinh tế học; United States,Hoa Kỳ